Person-organisation fit and turnover intention: the mediating role of work engagement - Memon, M.A. (Emerald Group Publishing Ltd., 2018)
Purpose: The purpose of this paper is twofold. First, it examines the impact of person-organisation fit (P-O fit) on work engagement (WE) and the impact of WE on turnover intention. Second, it examines the mediating role of WE between P-O fit and turnover intention. Design/methodology/approach: A cross-sectional online survey design was used to collect data through snowball sampling procedure. In total, 422 oil and gas (O&G) professionals participated in this study. In total, 13 incomplete samples were excluded during initial screening. As a result, 409 samples were used for final data analysis. The partial least squares-structural equation modelling, using SmartPLS3.0, was performed to test the hypothesised model. Findings: The results of the study revealed strong ties between P-O fit, WE, and turnover intention. Specifically, P-O fit was found to be a strong predictor of WE and WE is negatively related to employeesâ turnover intention. Further, WE mediated the relationship between P-O fit and turnover intention. Practical implications: The findings of this study suggest that O&G organisations must pay greater attention to P-O fit to increase employeesâ level of engagement and decrease voluntary turnover rate. Overall, the findings provide pragmatic insights for human resource management practitioners and the relevant stakeholders. Originality/value: To date, little attention has been devoted to understanding the mediating role of WE between P-O fit and turnover intention. The present study addresses this gap in the literature. Â© 2018, Emerald Publishing Limited.